Microwave Ablation of Hepatic Malignancy - Lubner, Meghan G.; Brace, Christopher L.; Ziemlewicz, Tim J.; Hinshaw, J. Louis; Lee, Fred T., Jr. (Seminars in Interventional Radiology, 2013)
Microwave ablation is an extremely promising heat-based thermal ablation modality that has particular applicability in treating hepatic malignancies. Microwaves can generate very high temperatures in very short time periods, potentially leading to improved treatment efficiency and larger ablation zones. As the available technology continues to improve, microwave ablation is emerging as a valuable alternative to radiofrequency ablation in the treatment of hepatic malignancies. This article reviews the current state of microwave ablation including technical and clinical considerations.
Keywords: interventional radiology; microwave; ablation; liver tumors